Simulation-Driven Design of a Portable Basketball Hoop System - Drew Burkhalter (Proceedings, 2020)
A simulation-driven design process is proven to generate improved, more robust, and cost-effective designs within a shorter design cycle. Incorporating simulation and optimization early in the design cycle helps shape the concept designs so fewer iterations and rework are necessary as the design matures. For this case study, a portable basketball hoop system is chosen for several reasons. This is a product that is common in everyday life, easily understood, and has several design challenges. To achieve the various design goals for this product, several optimization tools and simulation disciplines are coupled: multibody simulation to determine the kinematics and dynamics; finite element analysis to find displacements and stresses caused by external loads; topology optimization to define the essential structure to efficiently support the loads the product endures throughout its life cycle; and finally, multimodel optimization to consider all the loads when the structure is in several configurations during the optimization process.